Risks of Design Stage in Iraqi Construction Project (Journal of Engineering, 2018)
The management of construction projects needs to complete the basics of system management and work. Starting from the idea and how to turn it into a full study and ended at the construction project completion arriving at the purpose prepared for it, so the projects need to control on its operation and integration system in order to succeed.It is no secret for who concerned in construction projects field that the design stage is a very important stage in construction project because it determines the final features of the project through the requirements provided by the employer for the consultant to formulate it during this phase in the form of plans, drawings, and specifications, then translated on the ground as the shape of completed project meets those requirements.Therefore it has been necessary to focus in this paper on the design stage also demonstrated and analysis the most important risk facing this stage and their impact on a construction project by introducing a questionnaire to identify the most important risks factors at this stage affecting on the project.The paper had been shown that the effect of the design stage on Lump sum type of project contract was higher than the unit price, while the most important factor effect on a project its fast response of design team to prepare the design documents in order to facilitate the workflow and sequence of execution with effect level 3.714.